Necessity-Rich, Leisure-Poor: The Long-Term Relationship Between Income Cohorts and Consumption Through Age-Period-Cohort Analysis - Karonen Esa; Niemelä Mikko (SPRINGER INTERNATIONAL PUBLISHING AG, 2022)
The main aim of this study is to analyse household consumption patterns in the highest and lowest income quintiles and explore how they have changed over time and generations. Thus, the article explores whether social inclusivity through consumption has truly increased. This study utilises the cross-sectional time-series data of the Finnish Household Expenditure Surveys (HESs), covering the period 1966-2016. We use the Age-Period-Cohort Gap/Oaxaca (APCGO) model with logitrank dependent variables as the main statistical method. Our results indicate that an overall high income is advantageous with respect to income and spending, though the gap between high- and low-income groups has remained stagnant over cohorts. A more in-depth analysis reveals that the expenditure gap, in terms of necessities, food, and groceries consumption, has narrowed. Instead, income elastic-oriented spending on culture and leisure time has significantly increased in the high-income group, where the expenditure gap has expanded 60 percentage points over the cohorts. Simply put, expenditures on necessities have become more inclusive, but low-income groups are increasingly more 'leisure-poor'. Overall, high-income classes are spending an increasing amount of money on culture and leisure time over cohorts.